Table of Content - - (Journal of natural sciences, life and applied sciences, 2023)
Table of Content:1. Geochemistry of Clay Minerals Associated with Phosphates in Akashat Formation (middle Paleocene), Iraqi Western DesertProf. Kotayba Tawfiq Al-Youzbakey, Prof. Salim Mahmood Al-Dabbagh2. Spatial Analysis of Air Quality in the area of Imam Turki bin Abdullah Royal Reserve In the Kingdom of Saudi ArabiaProf. Ahmed Abdullah Al-Dughairi3. Wastewater treatment (The study of Wastewater treatment plants in Riyadh in terms of treatment methods and properties of treated water)Lecturer \ Najla Ali Alghonaimi4. The impact of water pollution on the spread of (malaria) in the state of Gezira, SudanDr. Amal Ibrahim Mohammed5. Characterization of zeolite ore in the west and south of the coastal chain – SyriaMrs. Nisreen Hosny Saflo , Prof. Moustafa Habib, Prof. Akel Rumie6. Rainfall variability and the risk of climatic drought in the Tensift basin (Morocco)Dr. El-Hawari Jawad, Prof. El-Ghachi Mohamed , Mr. Bouhafa Youness , Mr. Sinbri Abd-Ellatif
Keywords: Journal of Natural Sciences, Life and Applied Sciences